Assessing the Gene Content of the Megagenome: Sugar Pine (Pinus lambertiana). Issue 12 (1st December 2016) - Gonzalez-Ibeas, Daniel; Martinez-Garcia, Pedro J; Famula, Randi A; Delfino-Mix, Annette; Stevens, Kristian A; Loopstra, Carol A; Langley, Charles H; Neale, David B; Wegrzyn, Jill L
Abstract: Sugar pine ( Pinus lambertiana Douglas) is within the subgenus Strobus with an estimated genome size of 31 Gbp. Transcriptomic resources are of particular interest in conifers due to the challenges presented in their megagenomes for gene identification. In this study, we present the first comprehensive survey of the P. lambertiana transcriptome through deep sequencing of a variety of tissue types to generate more than 2.5 billion short reads. Third generation, long reads generated through PacBio Iso-Seq have been included for the first time in conifers to combat the challenges associated with de novo transcriptome assembly. A technology comparison is provided here to contribute to the otherwise scarce comparisons of second and third generation transcriptome sequencing approaches in plant species. In addition, the transcriptome reference was essential for gene model identification and quality assessment in the parallel project responsible for sequencing and assembly of the entire genome. In this study, the transcriptomic data were also used to address questions surrounding lineage-specific Dicer-like proteins in conifers. These proteins play a role in the control of transposable element proliferation and the related genome expansion in conifers.